2020
DOI: 10.1002/maco.202011709
|View full text |Cite
|
Sign up to set email alerts
|

N‐methyl‐2‐hydroxyethylammonium oleate ionic liquid performance as corrosion inhibitor for mild steel in hydrochloric acid medium

Abstract: The aim of the present study is to evaluate the performance of N-methyl-2hydroxyethylammonium oleate ([m-2HEA][Ol]) as a corrosion inhibitor for mild steel in a 0.1-mol/L hydrochloric acid solution and also investigate the role of chloride in the inhibition mechanism. This protic ionic liquid (PIL) has formerly shown a high efficiency as a corrosion inhibitor in a neutral chloride medium. Electrochemical and weight loss measurements, surface contact angle determination, scanning electron microscopy, and Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 98 publications
(183 reference statements)
0
3
0
Order By: Relevance
“…[43] In Table 2, the anodic (β a ) Tafel slopes, associated with the N80-CS dissolution (Fe!Fe 2 + + 2e À ), decreases markedly, suggesting that the N80-CS dissolution process is modified by the PCVIB adsorption, as similar to those reported in previous literature. [6,11,31,44] The reduction in β a may be ascribed to PCVIB that possess the nitrogen-hetercycle with the lone pair electron and the aromatic character, favoring the formation of Fe(II)-PCVIB complex. [6] By contrast, the cathodic (β c ) Tafel slopes could be considered to maintain constant to some extent, when the concentration is varied, proving that the reaction (2H + + 2e À !…”
Section: Potentiodynamic Polarization (Pdp) Curvesmentioning
confidence: 99%
“…[43] In Table 2, the anodic (β a ) Tafel slopes, associated with the N80-CS dissolution (Fe!Fe 2 + + 2e À ), decreases markedly, suggesting that the N80-CS dissolution process is modified by the PCVIB adsorption, as similar to those reported in previous literature. [6,11,31,44] The reduction in β a may be ascribed to PCVIB that possess the nitrogen-hetercycle with the lone pair electron and the aromatic character, favoring the formation of Fe(II)-PCVIB complex. [6] By contrast, the cathodic (β c ) Tafel slopes could be considered to maintain constant to some extent, when the concentration is varied, proving that the reaction (2H + + 2e À !…”
Section: Potentiodynamic Polarization (Pdp) Curvesmentioning
confidence: 99%
“…Our research group has previously found that PIL m-2HEAOL is an effective lubricant in its pure state [23] and in water-based formulations with talc and bentonite lubricating particles [24,25]. PIL m-2HEAOL also improves corrosion inhibition [26][27][28] and has low toxicity [29]. Despite these positive attributes, this molecule has yet to undergo testing for mechanical forming applications such as stamping.…”
Section: Introductionmentioning
confidence: 99%
“…[15] There are several ideas concerning the mechanism of corrosion inhibitors, including the soft and hard acid-base theory, passivation theory, and adsorption theory. [16] Furthermore, organic corrosion inhibitors may evenly passivate the metal surface, providing the metal with the best possible protection, whereas inorganic corrosion inhibitors generate a passivating coating that is extremely fractured and porous, causing local corrosion on the metal surface. [17] As a result, organic corrosion inhibitor research has been a popular issue in recent studies.…”
Section: Introductionmentioning
confidence: 99%